PERMODELAN GENANGAN BANJIR KALA ULANG PADA DAS KAHAYAN DI KOTA PALANGKA RAYA - Ravita Diah Fariskha (INFO-TEKNIK, 2025)
Rivers are one of the water resources that have a number of potentials that can be utilized for human welfare. Natural phenomena that threaten the existence of human life in several regions in Indonesia every rainy season are floods. Kahayan River is one of the rivers in Central Kalimantan that often experiences flooding. Kahayan River has an area of 81,684 km2, a length of 600 km, a width of 500 m and a depth of up to 7 m (Indonesia, 2016). Hydrologic Engineering Center-River Analysis System (HEC-RAS) software is a tool to determine the flow of water in a river. Simulation in HEC-RAS can be used to simulate floods well through steady flow and unsteady flow analysis. This research was conducted in the Kahayan River, Palangka Raya City, Central Kalimantan, starting from the Kahayan Bridge to Rambang Port. This research is included in the type of Exploratory Research, where researchers explore, analyze and generalize a phenomenon or condition through surveys and field observations. In this study, daily water level data is converted into daily discharge using the rating curve equation, discharge with a maximum value for 2013-2022 is determined to obtain the maximum annual discharge value. Based on the results of the discharge frequency analysis, the discharge for the 20, 50, and 100 year return periods is 1,459.2846 m³/s, 1,567.5594 m³/s, and 1,685.4194 m³/s, respectively. Return period discharge is one of the boundary conditions in flow simulation using 1-Dimensional HEC-RAS. Based on the simulation results, the maximum flood water level elevation for a 20-year return period is 4.98 m – 6.73 m. The 50-year return period ranges from 5.12 m – 6.9 m, while the 100-year return period is at an elevation of 5.27 m – 7.08 m.